2010
DOI: 10.1007/s12011-009-8601-9
|View full text |Cite
|
Sign up to set email alerts
|

Iodine, Selenium, and Other Trace Elements in Urine of Pregnant Women

Abstract: The purpose of this work was to determine trace element levels in urine and evaluate possible associations between urinary iodine concentration (UIC), other trace elements (Cr, Cu, Fe, Mn, Na, Se, Zn), toxic elements (Cd, Pb), anthropometrical measures (body weight and height), glycemic indices (serum insulin and glucose), and several parameters related to thyroid function (thyroid stimulating hormone, free thyroxine, antithyroid peroxidase antibodies, thyroid volume, and thyroid echogenicity) in pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
3
4
1
Order By: Relevance
“…Manganese (Mn; 3.0 mg/day as GM) daily intake was above the representative median Mn intake for men (2.1-2.3 mg/day). The mean concentrations and medians of the analyzed trace elements in whole blood and urine samples in most cases of this study can be regarded as comparable to the reference values previously reported [20,30,41]. However, the Mn level in urine was 4.24 μg/L, which lay outwith the 0.1-3.0 μg/L range [30].…”
Section: Toxic and Nutritional Element Profiles Of Healthy Males In Csupporting
confidence: 89%
See 2 more Smart Citations
“…Manganese (Mn; 3.0 mg/day as GM) daily intake was above the representative median Mn intake for men (2.1-2.3 mg/day). The mean concentrations and medians of the analyzed trace elements in whole blood and urine samples in most cases of this study can be regarded as comparable to the reference values previously reported [20,30,41]. However, the Mn level in urine was 4.24 μg/L, which lay outwith the 0.1-3.0 μg/L range [30].…”
Section: Toxic and Nutritional Element Profiles Of Healthy Males In Csupporting
confidence: 89%
“…However, it is necessary to take into consideration that the differences between element levels are indicative of individual variability, sex specificity, individual metabolic activity, environmental exposure, geological location, and dietary habits of the donors. These factors will contribute to the fact that certain values for some elements lie beyond normal ranges [2,41]. In this study, the median and mean values for urinary Fe exceeded the established reference ranges of those cited by Rodushkin and Odman [37] by one order of magnitude, whereas it is worth noting that the reference values reported by the quoted studies were not consistent …”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In the real samples, the recoveries were within the range of 82%-95% and 85%-92%, respectively, while for the CRM the values were in the range of 80%-84% and 93%-100%, respectively. Validation parameters are similar to those reported previously (Szybiń ski et al 2010;Praamsma et al 2011). The results of recovery study are in good agreement with criteria described by Schmidt and Michna (2007) to be between 80% and 120%.…”
Section: Analytical Performance Datasupporting
confidence: 89%
“…The first technique offers many advantages: high precision and sensitivity, low limits of detection, and rapid, multi-element quantification (Hsiung et al 1997). Several papers have reported on the determination of manganese in urine by ICP-MS (Townsend 2000;Szybiń ski et al 2010;Heitland and Kö ster 2004;Heitland and Kö ster 2006;Kumtabtim et al 2011). In two papers, most clinical samples were below LOQ (Heitland and Kö ster 2006;Kumtabtim et al 2011), additionally ICP-MS is sensitive to high concentration of salts in biological samples, which may cause signal suppression that cannot be corrected by the internal standard method.…”
Section: Introductionmentioning
confidence: 99%